CXC chemokine receptor 7 ameliorates renal fibrosis by inhibiting β-catenin signaling and epithelial-to-mesenchymal transition in tubular epithelial cells - Ping Meng; Chunli Liu; Jingchun Li; Ping Fang; Bo Yang; Wei Sun; Yunfang Zhang (Renal Failure)
Renal fibrosis is a common feature of various chronic kidney diseases. However, the underlying mechanism remains poorly understood. The CXC chemokine receptor (CXCR) family plays a role in renal fibrosis; however, the detailed mechanisms have not been elucidated. In this study, we investigated the potential role of CXCR7 in mediating renal fibrosis. CXCR7 expression is decreased in unilateral ischemia–reperfusion injury (UIRI) and unilateral ureteral obstruction mouse models. Furthermore, CXCR7 was specifically expressed primarily in the Lotus Tetragonolobus Lectin-expressing segment of tubules, was slightly expressed in the peanut agglutinin-expressing segment, and was barely expressed in the Dolichos biflorus agglutinin-expressing segment. Administration of pFlag-CXCR7, an overexpression plasmid for CXCR7, significantly inhibited the activation of β-catenin signaling and protected against the progression of epithelial-to-mesenchymal transition (EMT) and renal fibrosis in a UIRI mouse model. Using cultured HKC-8 cells, we found that CXCR7 significantly downregulated the expression of active β-catenin and fibrosis-related markers, including fibronectin, Collagen I, and α-SMA. Furthermore, CXCR7 significantly attenuated TGF-β1-induced changes in β-catenin signaling, EMT and fibrosis. These results suggest that CXCR7 plays a crucial role in inhibiting the activation of β-catenin signaling and the progression of EMT and renal fibrosis. Thus, CXCR7 could be a novel therapeutic target for renal fibrosis.